Development of Komodo Behavior E-Magazine Media (Varanus komodoensis) to Improve Understanding of Biological Concepts - Susanto, Lufty Hari; Istiana, Rita; Denih, Asep; Putri, Denisa Eka; Prasetyo, Teguh; Ichsan, Ilmi Zajuli (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2025)
This study aims to develop learning media in the form of an interactive e-magazine about the behavior of Komodo dragons (Varanus komodoensis) and evaluate its effectiveness in improving students' understanding of biological concepts and learning motivation. Media development was carried out using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The results of the needs analysis showed that students needed interesting and easily accessible digital media to understand animal behavior material. Validation by experts showed that the e-magazine media was very feasible to use, with a feasibility score of 93 from media experts and 95 from material experts. The implementation of media in learning resulted in a significant increase in conceptual understanding, with an N-Gain value of 0.7. The responses of teachers and students to the media were also very positive, with a satisfaction level reaching 98%. These findings indicate that e-magazines can be an effective innovative media in biology learning. Pengembangan Media E-Magazine Perilaku Komodo (Varanus komodoensis) Untuk Meningkatkan Pemahaman Konsep Biologi ABSTRAK: Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa e-magazine interaktif tentang perilaku komodo (Varanus komodoensis) serta mengevaluasi efektivitasnya dalam meningkatkan pemahaman konsep biologi dan motivasi belajar siswa. Pengembangan media dilakukan menggunakan model ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Hasil analisis kebutuhan menunjukkan bahwa siswa memerlukan media digital yang menarik dan mudah diakses untuk memahami materi perilaku hewan. Validasi oleh ahli menunjukkan bahwa media e-magazine sangat layak digunakan, dengan skor kelayakan sebesar 93 dari ahli media dan 95 dari ahli materi. Implementasi media dalam pembelajaran menghasilkan peningkatan signifikan dalam pemahaman konsep, dengan nilai N-Gain sebesar 0,7. Respons guru dan siswa terhadap media juga sangat positif, dengan tingkat kepuasan mencapai 98%. Temuan ini menunjukkan bahwa e-magazine dapat menjadi media inovatif yang efektif dalam pembelajaran biologi.